The Competence-Based Advanced Level Mathematics Curriculum: Implications for Students’ Enrolment in one University in Zimbabwe - Namatirai Chikusvura; Lwazi Sibanda; Joyce Mathwasa (RIRAI Publisher, 2021)
The study set out to examine the relevance of the competence-based Advanced Level mathematics curriculum for entry into university mathematics-related degree programmes. The study adopted a qualitative approach ingrained in the interpretive paradigm which employed a case study design. Four A-Level mathematics teachers, eighteen Lower Sixth and six Upper Sixth mathematics major students were purposively sampled to respond to semi-structured face-to-face interviews and focus group interviews. The study found that the implementation of the competence-based Advanced Level mathematics curriculum was negatively affected by incompetent teachers and supervisors, lack of resources and lack of support from other stakeholders. The study concluded that these impediments impacted negatively on students who aspired to pursue mathematics-related degree programmes at university and that there is a mismatch on the mathematics units in the competence-based Advanced Level mathematics curriculum and university requirements for mathematics-related degree programmes. The study recommends ministerial corroboration fostering university degree programmes requirements to be taught in high school, stakeholder involvement and continuous professional development for mathematics teachers and supervisors.